Mangamaru a creative indigenous Kapampangan folkdance (Philippines) - Santos, Michael E.; Tubera, Joel G.; Martin, Jonar T. (2015)
Dancing is a way to express one's feelings, to activate ones 'self, and to maintain a healthy lifestyle. Dance has been a part of human history since the earliest records of human life. Many people around the world view life as a dance from the eventual unfolding of social realities and the turn of the seasons which are reflected in the unique dance of every culture. The history of dance reveals the changes in the way people see the world, relate to their bodies, and experience the cycles of life. The dance research Mangamaru aimed to determine the cultural richness, artistry and ingenuity of the Kapampangan. it also aimed to show the Kapampangan's prevailing cultural values presented in the dance resulting to an increased awareness of national identity. In the process, the description of "mangamaru" cultural activity, instrumentation, costume and props, and choreography surfaces. The potential of the creative dance for public performance and inclusion in teaching physical education was also identified.
Keywords: Folk dancing -- Pampanga; Dance criticism; Mole crickets